Effects of Outdoor Walking on Positive and Negative Affect: Nature Contact Makes a Big Difference - Legrand, Fabien D.; Jeandet, Philippe; Beaumont, Fabien; Polidori, Guillaume (Frontiers in Behavioral Neuroscience, 2022)
It has been consistently demonstrated that physical exercise is a cost-effective way to promote emotional well-being. However, the environment in which it takes place might amplify or mitigate this beneficial effect. The present study aimed at comparing the effects of walking in a natural or urban field setting on positive and negative affect. In this purpose, one hundred fitfty students (46 female, 104 male; mean age: 20.2 years) were randomized into one of three groups: Green Walking (GW, n = 50), Urban Walking (UW, n = 50), or no-exercise (control) (CTRL, n = 50). Positive and negative affect ratings were collected for each participant before and after walking (or before and after attending a class in the CTRL group). Exercise parameters (duration, intensity, weather conditions, group size) were identical in the GW and UW groups. The walking routes differed in terms of vegetation density, proximity of water, presence of traffic, and amount of asphalted surfaces. Participants in the GW and UW groups reported significant reductions in negative affect pre- to post walking. However, positive affect was increased only for participants in the GW group. This finding may have meaningful implications for mental health professionals who treat patients with significant emotional distress or mood instability. Several explanations are discussed as potential mechanisms for the more beneficial effect of Green Walking, and presented as an important avenue for future research.